Pengalaman Orang dengan HIV AIDS Pengguna Napza Suntik Selama Menjalani Terapi Antiretroviral dan Metadon - Idramsyah Idramsyah; Agung Waluyo; I Made Kariasa (Journal of Telenursing (JOTING), 2019)
The aim of this research is to study the experience of People With HIV AIDS (PLWHA) Injection Drugs Users (IDUs) while undergoing anti-retroviral (ARV) and Methadone therapy. This qualitative research method uses a phenomenological approach. The interview transcript was analyzed by the Colaizi analysis stage. The analysis showed that ODHA of IDU felt physically normal and had a positive psychosocial life. Participants experience feelings of saturation with routine and obligation and are often seized with feelings of fear. PLWHA IDUs also experience side effects of concomitant ARV and Methadone therapy. Conclusion, Although PLWHA IDUs felt the benefits of therapy, they still experience various physical and psychosocial problems due to treatment procedures and ARV and Methadone treatment response. Keywords: Antiretroviral, HIV / AIDS, IDUs, Methadone, ODHA